Statistical Analysis of Some Selected Zooplakton Composition Dwelling Two Pan Marine Ecosystems with A Reference to the Abiotic Factors (Global Journal of Science Frontier Research, 2015)
Physical and chemical factors of marine ecosystems were measured in Anfoushy and Abu Qir Bay (Mediterranean Sea) Egypt during 2009 & 2010 and Northern and Southern Khobar during 2012 & 2013 to study their effect on the distribution of the zooplankton densities. Seasonal variations of water transparency (Secchi disc reading in cm) ; water temperature (°C) ; total dissolved solids (mg/l) ; total alkalinity (mg/l) ; total hardness (mg/l) ; salinity (g/l) ; chlorides (mg/l) ; total Nitrogen (mg/l) and Tributyl tin (μgg-1) were measured. Samples of the four pan marine beaches were taken at each site, using screw top polypropylene bottles of 1000 ml. capacity. The bottles were transported filled with distilled water and washed out and refilled with sea water at each site. Closing the bottles have been done underneath the water surface so as to make sure that they were completely full. These samples were returned to the laboratory and analyzed within twenty-four hours.
Keywords: water transparency; water temperature; total dissolved solids; total alkalinity; total hardness; salinity; chlorides; total nitrogen; tributyl tin; re